2021
DOI: 10.3389/fnut.2021.692504
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Genetic Variants in the SLC5A5 Gene and Associations With Breast Milk Iodine Concentration in Lactating Women of African Descent: The NUPED Study

Abstract: Background: The sodium iodide symporter is responsible for the transfer of iodine into breast milk and is encoded for by the SLC5A5 gene. The role of genetic variants in the SLC5A5 gene locus in relation to the transfer of iodine from plasma into breast milk in healthy lactating individuals has, to our knowledge, not been explored.Objective: To identify and characterize possible genetic variants of the SLC5A5 gene in women of African descent living in urban South Africa, and to study associations with breast m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…NIS gene mutations can affect the BMIC, as demonstrated in a case report of Japanese women with the homozygous NIS gene mutation T354P ( 236 ). A recent study in South African women identified 27 variants in the SLC5A5 gene coding for NIS ( 284 ). The study suggests that genetic variants of the SLC5A5 gene may influence BMIC, although the sample size was small and the study did not control for iodine intake.…”
Section: Iodine In Human Milkmentioning
confidence: 99%
“…NIS gene mutations can affect the BMIC, as demonstrated in a case report of Japanese women with the homozygous NIS gene mutation T354P ( 236 ). A recent study in South African women identified 27 variants in the SLC5A5 gene coding for NIS ( 284 ). The study suggests that genetic variants of the SLC5A5 gene may influence BMIC, although the sample size was small and the study did not control for iodine intake.…”
Section: Iodine In Human Milkmentioning
confidence: 99%
“…This is probably as a result of the recent maternal dietary iodine intake and duration of the lactation period [36,74,80]. Future studies are needed to investigate other factors, such as the genetic variations in the SLC 5 A 5 gene in relation to BMIC, which has been reported to play an important role in the iodine transfer into breast milk [81].…”
Section: Bmic As a Biomarker To Assess Iodine Status In Lactating Wom...mentioning
confidence: 99%